2014
DOI: 10.1063/1.4891103
|View full text |Cite
|
Sign up to set email alerts
|

Reference Correlation of the Viscosity of Cyclohexane from the Triple Point to 700 K and up to 110 MPa

Abstract: 19.12.14 KB. Ok to add published version to spiral, AIP polic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 159 publications
2
37
0
Order By: Relevance
“…14 Recently the work has been extended to cyclic and aromatic hydrocarbons. [15][16][17][18] The present study is a continuation of this effort. The aim of this work is to critically assess the data available in the literature, and provide a correlation for the viscosity of meta-xylene that is valid over a wide range of temperature and pressure, covering the vapor, liquid, and supercritical fluid states.…”
Section: Introductionmentioning
confidence: 97%
“…14 Recently the work has been extended to cyclic and aromatic hydrocarbons. [15][16][17][18] The present study is a continuation of this effort. The aim of this work is to critically assess the data available in the literature, and provide a correlation for the viscosity of meta-xylene that is valid over a wide range of temperature and pressure, covering the vapor, liquid, and supercritical fluid states.…”
Section: Introductionmentioning
confidence: 97%
“…From these deviations, we can also conclude that the experimental data are internally consistent to within the estimate experimental uncertainty. Equation (16) Figure 7, we compare the new results with data from the literature [13][14][15][16][17][18][19] at pressures up to 10 MPa as deviations from the correlation of Tariq et al 1 Our results agree well with the majority of the experimental data reported in the literature; however, the data of Rajagapol et al 17 at temperatures below 400 K and those of Grachev et al 19 to constrain the behavior of their correlation in the liquid state at temperatures above 441 K and those data are systematically higher than ours at temperatures above 450 K. Figure 8 compares our new results with data from the literature 13,14,[20][21][22][23][24][25][26][27][28][29] at pressure up to 10 MPa as deviations from the correlation of Huber et al 2,3 At temperatures up to 500 K, our new data agree with the correlation to within about ±1 %, which is the stated uncertainty of the correlation for the saturated liquid. At higher temperatures, the deviations are somewhat dependent upon pressure and span the interval (-3 to -6) %.…”
Section: Correlation Of the Viscosity Ratios At Low Temperatures Thmentioning
confidence: 83%
“…The first term in square brackets in equation (15) (15) were estimated from the correlations of Tariq et al 1 for cyclohexane and Huber et al 2,3 for decane and it was found that the effects of the temperature and pressure uncertainties contributed less than 0.8 % to ur(rη). The standard relative uncertainties ur(rη) are shown in Figure 5 for both fluids.…”
Section: Uncertainties Analysismentioning
confidence: 99%
See 2 more Smart Citations